COMPARATIVE STUDY OF PHYSIOLOGICAL AND PHENOTYPE CHARACTERISTICS OF JUNCUS RIGIDUS L. RHIZOME IN TWO REGIONS IN BASRAH GOVERNMENT (British Journal of Global Ecology and Sustainable Development, 2022)
The work was conducted at the tow zones north and southern regions on Basrah city in the south of Iraq to investigate the impact of polluted elements Pb,Cd,and Ni in rhizome of Juncus rigidus L. species ,it found by the results the analysis of polluting elements Pb,Cd and Ni in the rhizome of Juncus rigidus species the level of Pb was higher value than the rest of the other polluting elements ,phenotype of rhizome appearances less thick and dark brown in color and dense thick and stiff bristles in the polluted zone, measurements such as length ,thick, hairs number also considered in dimention.RWC it recorded a reduction rate of 49.45% compared to the control .Phenols and flavonoids content in rhizome has enhanced significantly at p≤0.05 within polluted, the highest level was recorded in the southern region of basrah was 4.8mg/gm and 2.7mg/gm. phenols content in polluted zone and control respectively and flavonoids was 2.9 mg/gm and 1.6 mg/gm in the polluted and control zone respectively.